Indigenous knowledge and practices approach to understanding disaster - Quilo, Queenie S.; Mabini, Mary Antoniette T.; Tamiroy, Nincie Pale O.; Mendoza, Myrma Jean A.; Viloria, Liwayway S.; Ponce, Sulpecia L. (2015)
Studies on disaster risks and management worldwide have made a strong case for the role of indigenous knowledge in preparing for, coping with, and surviving disasters. This study describes the indigenous knowledge and practices on disaster among the Subanen community in Zamboanga Peninsula, Southern Philippines. Based on data gathered from key informants, the study uncovered strong relationships among human, non-human (nature and animals), and the metaphysical in making sense of disasters. This interconnectivity is manifested in the Subanen's rich tradition of animism and in their disaster awareness based on their knowledge of animal warnings and signs in nature. Disasters are interpreted as Magbabaya's (Supreme Being) punishments for the community members' failure to perform their role as good stewards of natural resources. However, this is not to say that animistic cosmologies are the only means by which the community interprets disasters. Anthropogenic activities like illegal logging and forest denudation were also identified as culprits. While the Subanen acknowledge the power of nature and the metaphysical in shaping their lives, however, they are not passive actors who leave their fate to nature. Instead, they actively negotiate their fate especially during disasters by conducting rituals through which they connect their practices with that of the non-humans and the metaphysical.
Keywords: Natural disasters; Traditional knowledge; Sultan Kudarat (Mindanao); Subanuns